2018
DOI: 10.1371/journal.pone.0207677
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a fine-scale population stratification on rare variant association test results

Abstract: Population stratification is a well-known confounding factor in both common and rare variant association analyses. Rare variants tend to be more geographically clustered than common variants, because of their more recent origin. However, it is not yet clear if population stratification at a very fine scale (neighboring administrative regions within a country) would lead to statistical bias in rare variant analyses. As the inclusion of convenience controls from external studies is indeed a common procedure, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…For a given setting, power was similar in the different stratification situations, indicating that the correction method could maintain the power it would have in the absence of stratification. These results are in partial agreement with several studies reporting a small loss of power for PC-adjusted logistic regression in the presence of stratification relative to an absence of stratification [13, 20].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For a given setting, power was similar in the different stratification situations, indicating that the correction method could maintain the power it would have in the absence of stratification. These results are in partial agreement with several studies reporting a small loss of power for PC-adjusted logistic regression in the presence of stratification relative to an absence of stratification [13, 20].…”
Section: Discussionsupporting
confidence: 91%
“…Additional studies are required to investigate more complex genetic models, such as the presence of both risk and protective variants of a given gene, for which other association tests, such as variant-component approaches, may be more appropriate. Different results can be expected, as the effect of population stratification differs between testing strategies [17, 20]. In addition, the novel LocPerm strategy has not been evaluated in combination with other association tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The odds of disease conditional on covariates were estimated under a null model of no genetic association, and individual phenotypes were resampled, using these disease probabilities as individual weights, to obtain permuted data with a similar PS. However, subsequent studies showed that this procedure was less efficient than regular PC correction for dealing with fine-scale population structure (15). We show here that LocPerm , which uses the first 10 PCs weighted by their eigenvalues to compute a genetic distance matrix, handles complex and extreme PS more effectively than the standard PC-based correction approach, particularly in the context of small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of genetic structure is important to guide future studies of association both for common, but more importantly, for rare variants 40 . In the near future, interrogating the demographical history of France from genetic data will bring more precise results thanks to whole genome sequencing that, along with new methods, could allow testing formal models of demographic inference.…”
Section: Discussionmentioning
confidence: 99%